2018
DOI: 10.3897/mycokeys.35.25271
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological evidence reveal a new genus and species in Auriculariales from tropical China

Abstract: Grammatus labyrinthinus gen. et sp. nov. is proposed based on DNA sequences data and morphological characteristics. It is known so far from southern, tropical China. The new species is characterised by an annual, resupinate basidiocarp with a shallow, subporoid hymenophore, a hymenium restricted to the bottom of the tubes, a dimitic hyphal system, presence of encrusted skeletocystidia and dendrohyphidia, longitudinally septate basidia and smooth, oblong-ellipsoid to cylindrical, acyanophilous basidiospores. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Phylogenetic analyses based on ITS+nLSU DNA sequence data indicated that Heteroradulum belonged to Auriculariaceae, which showed that Heteroradulum was to be related to Grammatus H.S. Yuan & C. Decock [15]. Sequences of ITS and LSU nrRNA gene regions of the studied samples were generated, which showed that H. yunnanensis C.L.…”
Section: Introductionmentioning
confidence: 91%
“…Phylogenetic analyses based on ITS+nLSU DNA sequence data indicated that Heteroradulum belonged to Auriculariaceae, which showed that Heteroradulum was to be related to Grammatus H.S. Yuan & C. Decock [15]. Sequences of ITS and LSU nrRNA gene regions of the studied samples were generated, which showed that H. yunnanensis C.L.…”
Section: Introductionmentioning
confidence: 91%
“…Analisa secara deskriptif dilakukan melalui hasil pengamatan ciri-ciri morfologis dari setiap sampel jamur yang didapat. (Yuan et al 2018). Genus Auricularia merupakan anggota jamur yang paling umum dan terdistribusi luas, mulai dari tunggul, batang kayu hingga cabang pohon kayu.…”
Section: Analisis Dataunclassified
“…Morphological and phylogenetic analyses have provided more accurate identification and contributed to the definition of the taxonomic status of the genera in Steccherinaceae . In recent years, phylogenetic analysis based on multi-marker data has been widely used in the taxonomy of these fungi ( He and Dai 2012 ; Miettinen et al 2012 ; Binder et al 2013 ; Dai et al 2014 ; Miettinen and Ryvarden 2016 ; Justo et al 2017 ; Kotiranta et al 2017 ; Westphalen et al 2018 ; Yuan et al 2018 ; Yuan et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%